The economics of managerial taxes and corporate risk-taking - ARMSTRONG, Chris (Institutional Knowledge at Singapore Management University, 2019)
We examine the relation between managers’ personal income tax rates and their corporate investment decisions. Using plausibly exogenous variation in federal and state tax rates, we find a positive relation between managers’ personal tax rates and their corporate risk-taking. Moreover—and consistent with our theoretical predictions—we find that this relation is stronger among firms with investment opportunities that have a relatively high rate of return per unit of risk, and stronger among CEOs who have a relatively low marginal disutility of risk. Importantly, our results are unique to senior managers’ tax rates––we do not find similar relations for middle-income tax rates. Collectively, our findings provide evidence that managers’ personal income taxes influence their corporate risk-taking decisions.